Progressive Muscle Relaxation in Reducing Blood Glucose Level among Patients with Type 2 Diabetes - Agung Akbar, Muhammad; Malini, Hema; Afriyanti, Esi (Jurnal Keperawatan Soedirman, 2018)
Most of the treatments of patients with type 2 Diabetes MellitusÃ‚Â Ã‚Â (T2DM) who are admitted to the hospital in controlling the blood glucose still concentrated on medication and diet. On the other hand, exercise or activity management, however, gets insufficient consideration. Health professionals, especially nurses, need to be aware that some exercises or activities should be accomplished even for hospitalized patients. The effort to organize physical activity can be achieved by using Progressive Muscle Relaxation (PMR). The purpose of this study was to determine the effect of PMR on reducing the blood glucose levels in patients with T2DM. This research used the quasi-experimental design with one group pretest-posttest approach with control group design. The sampling technique was simple random sampling with 30 samples, 15 in both intervention and control groups. Data collection techniques were performed by measuring the blood glucose levels at that time. The duration of PMR as an intervention was performed for three days on a regular basis. Afterward, we remeasured the blood glucose levels. Data analysis was done by using t-test. The results of data analysis showed that there was a decrease in mean score of blood glucose levels for 63,80 mg/dl in the control group and 80,46 mg/dl in the intervention group.The results showed that PMR was effective in reducing the blood glucose levels of patients with T2DM in the public hospital (p-value = 0.015). The results of this study can be applied by nurses as an alternative intervention in the management of patients with T2DM.Ã‚Â